Intergenerational Coresidence and Female Labour Supply - Andreas Landmann; Helke Seitz; Susan Steiner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We examine the role of family structure, specifically of co-residence with parents in-law, for female labour supply. To account for the endogeneity of co-residence, we exploit a tradition in Central Asia, namely that the youngest son of a family usually lives with his parents. Using data from Kyrgyzstan, we therefore instrument co-residence with being married to a youngest son. We find that the effect of co-residence on female labour supply - though insignificant - tends to be negative.
Keywords: J12; J21; 330